Kontinuitas Arsitektur pada Bangunan Adaptive Reuse di Kotabaru Yogyakarta - Nabila Aufelisa; Dwita Hadi Rahmi (Arsir: Jurnal Arsitektur, 2024)
Kotabaru is a cultural heritage area which has quite unique legality and history, an area that has existed since 1920 with the concept of a garden city to accommodate the Dutch community at that time until currently the Kotabaru area has changed functions, especially to the function of cafes and restaurants if it refers to a recommended study for the Kotabaru area, this activity is called adaptive reuse which creates continuity in buildings in the Kotabaru area, therefore this research was carried out to see how continuity occurs in buildings in the Kotabaru area using several case studies and parameters from previous research, the method used in this research is descriptive qualitative and it is hoped This research can show what aspects are maintained and the level of continuity they have.